2017
DOI: 10.2116/analsci.33.239
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Alkyl Diamide Amine and Water-soluble Diamide Ligand for Separating of Am(III) from Cm(III)

Abstract: Alkyl diamide amine (ADAAM), a new high-performance reagent with a simple structure, was examined for the mutual separation of Am(III) and Cm(III). The combination of ADAAM and N,N,N′,N′-tetraethyldiglycolamide (TEDGA) as a masking agent shows selectivity for Am(III) over Cm(III) in highly acidic media with separation factors of up to 41.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…From an aqueous phase of containing 0.001 mol L -1 TEDGA in 1.5 mol L -1 HNO3 spiked with Am(III) and Cm(III), with 0.75 mol L -1 ADAAM(EH) in n-dodecane SFAm/Cm = 5.7 was achieved (DAm > 1, DCm < 1). [30] The feasibility of the Am(III)/Cm(III) separation was demonstrated on a counter-current mixer settler test, which allowed the recovery of 99.8 % Am(III) with only 9.6 % of Cm(III) impurity in the product. [31] The solvent composed of 0.25 mol L -1 ADAAM(EH) and the feed contained 1.5 mol L -1 HNO3 spiked with Am(III) and Cm(III) without the use of the aqueous complexant, TEDGA.…”
Section: Introductionmentioning
confidence: 99%
“…From an aqueous phase of containing 0.001 mol L -1 TEDGA in 1.5 mol L -1 HNO3 spiked with Am(III) and Cm(III), with 0.75 mol L -1 ADAAM(EH) in n-dodecane SFAm/Cm = 5.7 was achieved (DAm > 1, DCm < 1). [30] The feasibility of the Am(III)/Cm(III) separation was demonstrated on a counter-current mixer settler test, which allowed the recovery of 99.8 % Am(III) with only 9.6 % of Cm(III) impurity in the product. [31] The solvent composed of 0.25 mol L -1 ADAAM(EH) and the feed contained 1.5 mol L -1 HNO3 spiked with Am(III) and Cm(III) without the use of the aqueous complexant, TEDGA.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the ligand selectivity can be improved by tuning the ligands. Thus, many experiments and calculations have been dedicated to the search for efficient ligands, such as BTPs, 6,6′-bis­(5,6-dialkyl–1,2,4-triazin-3-yl)-2,2′-bipyridine (BTBPs), 2,9-bis­(1,2,4-triazin-3-yl)-1,10-phenanthroline (BTPhens), 6,6″-bis­(1,2,4-benzotriazin-3-yl)-2,2′:6′,2″-terpyridines (BTTPs), and N , N , N ′, N ′-tetrakis­(2-pyridylmethyl)­ethylenediamine (TPEN) as soft donors ligands. Among the tested ligands, soft N donors, hard O donors, and mixed ‘N, O’ donors belong to Lewis bases in terms of hard and soft acids and bases theory (HSAB) . Conversely, trivalent Am and Eu ions pertain to hard Lewis acids with a large ionic radius and relatively positive charge .…”
Section: Introductionmentioning
confidence: 99%
“…To understand the molecular mechanism of the extraction process, various theoretical studies , , have been carried out, characterizing the molecular structure and electronic distribution of Am­(III)/Eu­(III) complexes with different extractive ligands using the natural bond orbital (NBO) or quantum theory of atoms in molecules (QTAIM). It was found that the electrostatic interaction between ligands and metal ions could be regulated by the selection of ligands.…”
Section: Introductionmentioning
confidence: 99%
“…As DA-typed ligands, 2-ethylhexyl diamide amine (ADAAM(EH)) and ethyl diamide amine (ADAAM(Et)) were used as hydrophobic and hydrophilic ligands, respectively. 13…”
Section: Introductionmentioning
confidence: 99%